Water and sediment ecotoxicological assessment in a river affected by former mining activities - Morais, Lucas G. [UNESP]; Perina, Fernando C. [UNESP]; Davanso, Marcela B. [UNESP]; Buruaem, Lucas M.; Rodrigues, Valéria G.S.; Sígolo, Joel B.; Abessa, Denis M.S. [UNESP] (My University, 2013)
During most of the 20th century, the Ribeira de Iguape River Basin experienced intense activity related to mining. As consequence, it is estimated that the Ribeira de Iguape River received the discharges of approximately 5.5 tons. month-1 of residues rich in As, Cd, Pb, Cu, Cr and Zn. In this study samples of sediment and water were collected at five sampling sites distributed along the river, with the purpose of evaluating environmental quality. To achieve that, chemistry analysis was performed for As, Cd, Pb, Zn, Ni, Mn, Fe, Cr, Al and Cu, together with acute toxicity tests with Daphnia similis. The results showed that for all the samples, metals concentrations were below the quality criteria adopted by the State Environmental Agency for both waters and sediments; additionally, no toxicity was observed. The absence of acute toxicity and the low levels of metals are indicative of satisfactory environmental conditions, corroborating to the literature reporting to decreasing contamination by lead and other metals. However, for sediments, higher concentrations of metals were found along the river, in comparison to the reference site, indicating recovery was not totally achieved.
Keywords: Contamination; Daphnia similis; Metals; Ribeira de iguape river; Toxicity